The relationship between primary school heads' personality traits and school performance in the district of Melaka Tengah / Kamariah Mohd Dawam - Mohd Dawam, Kamariah (2013)
School performance is dependent on the leadership of the school heads and teachers. However, teachers' perceptions towards their principals' personalities indicate an important dimension to evaluate the leaders' capacities. Leadership traits and personality are important in order to increase organizational performance. Therefore, the purpose of this study was to examine the relationship between primary school heads' personality traits and school performance in the District of Melaka Tengah. A total of 57 primary school heads in the district of Melaka Tengah completed surveys for this study. Data were collected using the survey method and were analyzed using both descriptive and inferential statistics. Based on the data collected, the findings showed that generally the primary schools performance was at Band 2, which was considered a very good performance. The result also showed that there was a positive relationship between assertive and school performance. The findings of this study have implications to the role of primary school heads in developing their personality traits in enhancing school performance.